Clinical Presentation of Attention-Deficit Hyperactivity Disorder Symptoms in Terms of Gender and Chronological Age - Ahmad Ghanizadeh; Alireza Salehi; Seyed Reza Moeini (Shiraz University of Medical Sciences, 2019)
The present cross-sectional study aimed to evaluate Attention-deficit hyperactivity disorder (ADHD) symptoms in terms of gender and age. Based on convenience sampling, the data records of 1,184 children and adolescents with ADHD were gathered from various Child and Adolescent Psychiatry Clinics affiliated to Shiraz University of Medical Sciences (Shiraz, Iran). During 2010-2015, the patients had been interviewed face-to-face for ADHD diagnosis in accordance with the Diagnostic and Statistical Manual of Mental Disorders 4th Edition (DSM-IV) diagnostic criteria. The collected data were re-analyzed using parent-reported ADHD symptoms measured with the DSM-IV clinical symptoms checklist. Statistical analysis was performed using SPSS software with the Pearson correlation test, Chi-square test, and t test. PThe mean age of the participants was 9.29±2.55 years, 904 (76.40%) of whom were boys. The mean total score of hyperactivity-impulsivity in girls and boys was 2.63±2.77 and 3.19±8.17, respectively. The mean total score of inattention in girls and boys was 3.40±1.97 and 3.28±2.00, respectively. Age and gender were not associated with the symptoms of inattentive ADHD. The symptoms associated with hyperactivity-impulsivity had a significant association with age (P<0.05). The symptoms with a statistically significant association with gender were frigidity (P=0.001), often running about (P=0.03), and often difficulties with playing or leisure activities (P=0.005). The most common symptoms of inattentive ADHD in both boys and girls were "inattention to details or making careless mistakes" (47.6% and 54.3%, respectively) and "fails to finish work" (43.0% and 40.1%, respectively). In contrast with the hyperactivity-impulsivity, the severity of inattention was not associated with age. The results of the present study indicated that while the ADHD screening questions for inattention could be the same for both genders, they should be different for hyperactivity-impulsivity.